Looking Beyond Rape and War – The Need to Take Violence Prevention Seriously in Women, Peace and Security: Potreba ozbiljne prevencije nasilja u miru i sigurnosti žena - Myrttinen, Henri; Lopez Castaneda, Diana (Journal of Regional Security, 2022)
In the two decades since its inception, the Women, Peace and Security (WPS) agenda has arguably had its greatest impact in terms of opening up discussions on women in conflict, in opening up security sector institutions for women and in setting up new mechanisms to try to counter conflict-related sexual violence. While this is in many ways commendable, this has also led to the militarisation of WPS, a narrow focus only on particular forms of gender-based violence, and led to a disengagement with the overarching goal of preventing armed violence in the first place. It has also led to a false perception that WPS only relates to armed conflict. Furthermore, where WPS-related consultation and participation mechanisms have been set up, these are often side-lined in times of crisis. Drawing on experience from working on WPS issues in various contexts, we argue for a fundamental re-think of the approach to ‘prevention’ in WPS, for a strengthening of the ‘peace’ element of WPS, and for a closer linking of WPS with other agendas such as climate change response, disarmament, social inequality, corruption, broader gender equality and gender transformation for the agenda to go beyond ‘making war safe for women.’ These shifts need to be properly reflected in national and local implementation of WPS but also based on a more intersectional and comprehensive approach to gender.